1996
DOI: 10.1128/aac.40.3.627
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-hour area under the concentration-time curve/MIC ratio as a generic predictor of fluoroquinolone antimicrobial effect by using three strains of Pseudomonas aeruginosa and an in vitro pharmacodynamic model

Abstract: Several investigators have suggested that the 24-h area under the concentration-time curve (AUC)/MIC ratio (AUC/MIC24 or AUIC24) can be used to make comparisons of antimicrobial activity between fluoroquinolone antibiotics. Limited data exist regarding the generic predictive ability of AUC/MIC24 for the antimicrobial effects of fluoroquinolones. The purposes of the present investigation were to determine if the AUC/MIC24 can be used as a generic outcome predictor of fluoroquinolone antibacterial activity and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
2
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(75 citation statements)
references
References 16 publications
3
68
2
2
Order By: Relevance
“…On the other hand, C max /MIC, AUC/MIC, and T eff were not predictive of in vitro and in vivo effects produced by seven antibiotics, including ciprofloxacin and fleroxacin [34]. Similarly, AUC/MIC determined over a 24-hour period (AUC 24 /MIC or AUC) did not predict the effects of four quinolones, in an in vitro, dynamic model [38], which contrasts with data reported in a model using two other quinolones [37]. At first glance, these and similar contradictions between reported optimal predictors may seem incompatible.…”
Section: Predictors Of the Antimicrobial Effectcontrasting
confidence: 61%
“…On the other hand, C max /MIC, AUC/MIC, and T eff were not predictive of in vitro and in vivo effects produced by seven antibiotics, including ciprofloxacin and fleroxacin [34]. Similarly, AUC/MIC determined over a 24-hour period (AUC 24 /MIC or AUC) did not predict the effects of four quinolones, in an in vitro, dynamic model [38], which contrasts with data reported in a model using two other quinolones [37]. At first glance, these and similar contradictions between reported optimal predictors may seem incompatible.…”
Section: Predictors Of the Antimicrobial Effectcontrasting
confidence: 61%
“…Among the currently available fluoroquinolones moxifloxacin is characterized by significantly improved pharmacodynamic properties against both gram-positive and gram-negative bacteria, in particular as high concentrations at the focus of infection translate into an augmented killing of the causative pathogens irrespective of their penicillin and/or macrolide susceptibilities, or even QRDR mutations. Several investigators have also studied the pharmacodynamics of various fluoroquinolones and have shown that quinolones differ in their pharmacodynamic properties, even if their antibacterial activities are almost identical [63,[68][69][70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…Newer dosing strategies also have been employed for concentration-dependent antimicrobials to optimize their pharmacodynamic properties and maximize efficacy. Such strategies include the use of extendedinterval dosing regimens for aminoglycosides and the use of high doses of fluoroquinolones to achieve high concentrations relative to the pathogen MICs [56][57][58].…”
Section: Application Of Pharmacokinetic and Pharmacodynamic Principlesmentioning
confidence: 99%